1992
DOI: 10.1007/bf00156573
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations in the electroretinographic c-wave and retinal melatonin content in rats with inherited retinal dystrophy

Abstract: The inability of retinal pigment epithelium to phagocytose shed photoreceptor disks is a cause of retinal degeneration in the Royal College of Surgeons rat; retinal pigment epithelial phagocytosis and disk shedding are regulated by the diurnal rhythm of retinal melatonin level. The diurnal rhythms of the electroretinogram (particularly that of the retinal pigment epithelial potential, the electroretinographic c-wave) and retinal melatonin content were thus investigated in Royal College of Surgeons rats from po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…After a minimum occurring about 1-1.5 hours after the expected onset of room illumination in the morning, an increase in the b-and c-wave amplitudes was seen [25]. In the present study, the amplitudes of the a-, b-and c-waves recorded in response to the initial light stimulus of each series increased between the first (8-minute interstimulus interval) and the last (70-second interstimulus interval) series of experiments performed during the day (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…After a minimum occurring about 1-1.5 hours after the expected onset of room illumination in the morning, an increase in the b-and c-wave amplitudes was seen [25]. In the present study, the amplitudes of the a-, b-and c-waves recorded in response to the initial light stimulus of each series increased between the first (8-minute interstimulus interval) and the last (70-second interstimulus interval) series of experiments performed during the day (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…Sandberg et al [24] and Hawlina et al [25] observed diurnal changes in ERG amplitudes recorded from normal rats. After a minimum occurring about 1-1.5 hours after the expected onset of room illumination in the morning, an increase in the b-and c-wave amplitudes was seen [25].…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, measurements of corneofundal potential (electro-oculogram) were carried out as early as in 1966 to measure retinal pigment epithelial function of dystrophic Royal College of Surgeons (RCS) rats with defective retinal pigment epithelial phagocytosis [11]. The method described here enables recording of the c-wave simultaneously with other components of the ERG, which may be helpful in a combined study of retinal and RPE dysfunctions, such as in RCS rats [3,5,9].…”
Section: Discussionmentioning
confidence: 99%
“…Preparatory procedures are described in detail elsewhere [9]. Briefly, anesthetized pigmented rats (1.5 g/kg of urethane intraperitoneally; pupils dilated by 1% atropine) were placed in a stereotaxic frame with earbars and a mouthbar (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…[45][46][47] Although the dopamine receptor is distributed throughout the retina in rodents, 48 intravitreal administration of dopamine suppresses the third-order neuronal response more than the second-order neuronal response. 49 Therefore, depletion of intraretinal dopamine could result in augmentation of the third-order neuronal response.…”
Section: Mechanism Of Preservation Of the Third-order Neuronal Responsementioning
confidence: 98%